Lower Body Positive Pressure Application with an Antigravity Suit in Acute Carotid Occlusion - Karine Berthet; Anne Claire Lukaszewicz; Marie-Germaine Bousser; Didier Payen (Stroke Research and Treatment)
The challenge in acute stroke is still to reperfuse as early as possible the ischemic territory. Since fibrinolytic therapies have a limited window with potential risk of bleeding, having a nonpharmacologic mean to recruit vessels in area surrounding necrosis might be useful. We propose here to use antigravity suit inflated at “venous” pressure levels to shift blood towards thoracic and brain territories. We report two cases of spectacular clinical recovery after acute carotid occlusion.